Can international students in china affect Chinese OFDI: Empirical analysis based on provincial panel data - Shaoming Cheng; Yuheng Lin; Xinyi Zhu; Ahsan Akbar (Economies, 2019)
The present study employs panel data of 29 provinces and municipalities in mainland China from 2003 to 2016 to empirically investigate the influence of international students on China's outward FDI. The results show that international students in China can significantly promote outward FDI in various Chinese provinces. Moreover, we observe a substitution effect with export scale and wage level, that is, attracting international students can offset the negative impact of insufficient export scale and low wages on regional OFDI (outward foreign direct investment). From a regional perspective, the growth in international students' inflows in China has a significant positive impact on OFDI of provinces along 'the 21st Century Maritime Silk Road', but has no significant impact on the provinces along 'the Silk Road Economic Belt'. The above conclusions not only elaborate the regional distribution mechanism of OFDI in China, but also provide a reference for each province to formulate more favorable policies to attract foreign talent to effectively implement the strategy of 'going global'.
Keywords: F21; F22; 330; “ The Belt and Road” export scale; international students in China; outward FDI; wage level